2021
DOI: 10.1111/cdoe.12631
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department use for nontraumatic dental conditions among children and adolescents: NEDS 2014‐2015

Abstract: Objectives: Despite great efforts to improve paediatric dental care access in the last two decades, the use of emergency departments (ED) for dental conditions among children that are more appropriately addressed in dental offices remains a public health concern in the United States. We examined factors associated with ED visits for nontraumatic dental conditions or NTDCs and ED visits for any other reason among children and adolescents.Methods: A retrospective secondary data analysis of ED visits was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…dental caries) in different countries and health systems. [12][13][14][15] The intersection between DC as a Public Health issue and its treatment in inpatient settings raises the question: how does the Brazilian Unified Health System (SUS) fit into this scenario?…”
Section: Introductionmentioning
confidence: 99%
“…dental caries) in different countries and health systems. [12][13][14][15] The intersection between DC as a Public Health issue and its treatment in inpatient settings raises the question: how does the Brazilian Unified Health System (SUS) fit into this scenario?…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines consider the diagnosis and management of fractures, luxations and avulsions of both the primary and permanent dentition. Nontraumatic dental conditions (NTDC) are therefore any diagnosis that is not traumatic in nature and commonly includes dental caries, periapical abscesses, facial cellulitis, periodontal disease and acute presentations of oral pathology 6 . Given the vast range of possible diagnoses, there is no classification of NTDC.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide NTDC place a significant strain on emergency departments (EDs) of tertiary hospitals 6 . One study from the United States of America (USA) demonstrated an increase in dental presentations in EDs over the past 10–20 years 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations